EVALUATING THE CAUSES AND CONSEQUENCES OF INTERNAL DISPLACEMENT OF PERSONS IN KADUNA STATE - Ibrahim, Aliyu H.; Yaro, Nura Alhaji; Ibrahim, Murjanatu Yahaya; Adama, Yusuf (FUDMA Journal of Sciences, 2022)
The constraints faced by IDPs were many ranging from inadequate housing, poor medical health care, hazardous work, vulnerability of women and children to trafficking and sexual exploitation, discrimination based on ethnicity, religion, class or gender as well as break in social relations. The aim of the study was to assess the nature of internal displacement in terms of causes and consequences of the internally displaced persons in Kaduna State. The sample population was drawn from the three senatorial zones. Purposive/availability sampling was used in selecting the settlements. The results had shown movement of internally displaced persons (IDPs) from one local government to another and from neighboring states into the study area. The study also revealed that the level of integration between the IDPs and the host communities is higher in rural areas as a result of the small size of the settlements which allows easier cohesion between the communities. The study recommended for public awareness on the large number of IDPs presence in the society and the need to empower them. The virtue of tolerance and forgiveness should be encouraged among the people to strengthen mutual co-existence in the society.
Keywords: Consequences, Communities Displacement, Internal and Sources